How Did the Pitch Clock Impact the 2023 Major League Baseball Season? - Kriter, Andrew; Sommers, Paul (Journal of Student Research, 2024)
Major League Baseball implemented a pitch clock in 2023 to speed up the game. The authors explore the impact of the pitch clock on average game time, home attendance, and several common team pitching metrics [earned run average (ERA) and walks plus hits per inning pitched (WHIP)]. For the 83 starting pitchers who pitched for the same ball club in 2022 and 2023, the authors use Bill James’s Game Score to assess their performance at home between the two seasons. Games were about 13 percent shorter, attendance increased for most clubs, and overall team pitching suffered (team ERAs and WHIPs, on average, increased). While average Game Score decreased for close to 60 percent of starting pitchers from 2022 to 2023, the drop-off was statistically significant in only six cases.